Effect of sintering additives size on the microstructure and wear properties of Al2O3 ceramics. (10th December 2017) - Xu-Guo, Huai; Zi-Shang, Chen; Xiao-Ping, Liang; Sheng, Bi
ABSTRACT: Al2 O3 ceramics was sintered at low-temperature by using sintering additives. The effect of the particle size of TiO2 sintering additive on the microstructure and friction-wear properties of Al2 O3 ceramics was studied by using XRD and SEM. The bulk density and hardness of the Al2 O3 ceramics were tested by Archimedes's method and the microhardness meter, respectively. M-2000 friction and wear test machine was used to analyze the friction and wear properties. The results show that with the increase of sintering temperature (1300-1500°C), the density and hardness of Al2 O3 ceramics with 1.5wt.% TiO2 increased, while the friction coefficient and wear rate decreased. At the same sintering temperature, the friction coefficient and wear rate of Al2 O3 ceramics with nano TiO2 is lower than that of with micro TiO2, that is, the sintering of Al2 O3 ceramics was positively affected by nano TiO2 significantly. The main wear mechanisms of Al2 O3 ceramics sintered at lower temperature are brittle fracture wear, and the wear of Al2 O3 ceramics prepared at high temperature was dominated by plastic deformation characterized with microcutting.